Seasonal and Sexual Differences in the Microbiota of the Hoopoe Uropygial Secretion - Rodríguez-Ruano, Sonia M; Martín-Vivaldi, Manuel; Peralta-Sánchez, Juan M; García-Martín, Ana B; Martínez-García, Ángela; Soler, Juan J; Valdivia, Eva; Martínez-Bueno, Manuel (Genes, 2018)
The uropygial gland of hoopoe nestlings and nesting females hosts bacterial symbionts that cause changes in the characteristics of its secretion, including an increase of its antimicrobial activity. These changes occur only in nesting individuals during the breeding season, possibly associated with the high infection risk experienced during the stay in the hole-nests. However, the knowledge on hoopoes uropygial gland microbial community dynamics is quite limited and based so far on culture-dependent and molecular fingerprinting studies. In this work, we sampled wild and captive hoopoes of different sex, age, and reproductive status, and studied their microbiota using quantitative polymerase chain reaction (qPCR), fluorescence in situ hybridization (FISH) and pyrosequencing. Surprisingly, we found a complex bacterial community in all individuals (including non-nesting ones) during the breeding season. Nevertheless, dark secretions from nesting hoopoes harbored significantly higher bacterial density than white secretions from breeding males and both sexes in winter. We hypothesize that bacterial proliferation may be host-regulated in phases of high infection risk (i.e., nesting). We also highlight the importance of specific antimicrobial-producing bacteria present only in dark secretions that may be key in this defensive symbiosis. Finally, we discuss the possible role of environmental conditions in shaping the uropygial microbiota, based on differences found between wild and captive hoopoes.
Keywords: mutualism; microbiota; clostridia; high-throughput sequencing; quantitative polymerase chain reaction (qPCR); uropygial gland secretion; hoopoe; fluorescence in situ hybridization (FISH); bacteria